Bimbingan Spiritual di Hospital Mesra Ibadah (HMI) Di Malaysia: Kajian Kes - Abu Bakar, Mohd Zainuddin; Ashaari, Muhamad Faisal; Abdul Jalil, Siti Jamiaah; bin Muhamad, Norhisham (Borneo International Journal of Islamic Studies, 2020)
The worship-friendly hospital program (HMI) is one of the initiatives by the Ministry of Health (MOH) carried out amongst the public hospitals in Malaysia, especially in Selangor. This is established in 2016 for the holistic treatment purposes. This article attempts to examine the valuable points of the spiritual guidance managed to assist in improving the healing process of HMI patients. The approach was deployed through structured interviews amongst Head of Islamic Affairs Unit together with hospital volunteers. There were six pilot hospitals in the State of Selangor having implemented HMI since 2016. The finding reveals that there are three strategic approaches of spiritual guidance, namely counselling, guidance, emotional and psychological strengthening (psychotherapy) used to assist the patients’ healing process. As such, these three strategic approaches were implemented, while each of them operates with their specific way referring to both knowledge and experience. The approach of counselling and guidance was deployed regularly but for emotional and psychological reinforcement (Psychotherapy) approaches it was not possible to properly implement the skills constraints of the staff involved. This approach was based more on experiential built on hospital cases. Hospital patients not only need clinical care, but they also need spiritual guidance to help with treatment and recovery efforts. Comprehensive and holistic patient medical management is essential to ensure that patients are able to recover as usual and that the healing process is ongoing.